Peningkatan Kemampuan Komunikasi Interpersonal pada Siswa Sekolah Menengah Kejuruan (Smk) 'X' di Yogyakarta Melalui Pelatihan Asertivitas - Arzia Purita; Sumedi P. Nugraha; Uly Gusniarti (Universitas Islam Indonesia, 2015)
The purpose of this research was to empirically examine the effect of assertiveness training on the students interpersonal communication skills. The research design was pretes postest control group design. The subject determination into experimental group and control group. Interpersonal communication skills is measured by using scale interpersonal communication skills based on interpersonal communication aspects of DeVito (2011). Data analysis on this research was mixed design anova. The result of this research revealed the existance of interaction between time (pretest and posttest) and group (experimental and control) that was stated by F = 41,786; P = 0,000. The result showed that control group and experimental group was different. In this research, the asertiveness training treatment contribution toward the increasing of interpersonal communication skills is 79,1%. Key words: Asertiveness training, Interpersonal communication skill, Vocational high school.